City Regions and Devolution in the UK The Politics of Representation - Beel, David (Civil Society and Social Change series, 2021)
"EPDF and EPUB available Open Access under CC-BY-NC licence. Rich in case study insights, this book provides an overview of city-region building and considers how governance restructuring shapes political, economic, social and cultural landscapes. Reviewing the Greater Manchester, Sheffield, Swansea Bay City Regions, Cardiff Capital Region and the North Wales Growth Deal, the authors address the tensions and opportunities for local elites and civil society actors."